Evidence that Altered Cis Element Spacing Affects PpsR Mediated Redox Control of Photosynthesis Gene Expression in Rubrivivax gelatinosus - Shimizu, Takayuki; Cheng, Zhuo; Matsuura, Katsumi; Masuda, Shinji; Bauer, Carl E. (PLOS ONE, 2015)
PpsR is a major regulator of photosynthesis gene expression among all characterized purple photosynthetic bacteria. This transcription regulator has been extensively characterized in Rhodobacter (Rba.) capsulatus and Rba. sphaeroides which are members of the α-proteobacteria lineage. In this study, we have investigated the biochemical properties and mutational effects of a ppsR deletion strain in the β-proteobacterium Rubrivivax (Rvi.) gelatinosus in order to reveal phylogenetically conserved mechanisms and species-specific characteristics. A deletion of the ppsR gene resulted in de-repression of photosystem synthesis showing that PpsR functions as a repressor of photosynthesis genes in this species. We also constructed a Rvi. gelatinosus PpsR mutant in which a conserved cysteine at position 436 was changed to an alanine to examine whether or not this residue is important for sensing redox, as reported in Rhodobacter species. Surprisingly, the Cys436 Ala mutant retained the ability to repress photosynthesis gene expression under aerobic conditions, suggesting that PpsR from Rvi. gelatinosus has different redox-responding characteristics. Furthermore, biochemical analyses demonstrated that Rvi. gelatinosus PpsR only shows redox-dependent binding to promoters with 9-bp spacing, but not 8-bp spacing, between two PpsR-recognition sequences. These results indicate that redox-dependent binding of PpsR requires appropriate cis configuration of PpsR target sequences in Rvi. gelatinosus. These results also indicate that PpsR homologs from different species regulate photosynthesis genes with altered biochemical properties.